Can Small and Medium Enterprises Survive in MEA 2025: A Case Study of Agro-industry SMEs in Indonesia - Novi Haryati; Apichaya Lilavalicakul; Moch Adi Surrahman (APMBA (Asia Pacific Management and Business Application), 2019)
Food processing agro-industry is a creative industry which immensely contributes to economic development, employment, and Gross Domestic Product (GDP) in Indonesia. Competitiveness is a combination of successful inside and outside of Small Medium Enterprise. Thus, this research aims to 1) get an overview related to the SME food sector and its competitiveness, and 2) understand the influence of entrepreneurial marketing and government policy to Tempe (soybean-cake) chips SME’s competitiveness by using Structural Equation Model (SEM) toward MEA 2025. This quantitative research is using 64 soybean cake chips entrepreneurs as a sample purposively. Data analysed with Entrepreneurial Marketing concept in 7 dimensions, and SEM PLS to understand the relation between the important factors in developing SME market. The result shows that the government policy is insignificant, influential policy but the effect is inconsiderably significant because there is actually technological assistance which is not targeted yet. Regarding capital, the craftsmen prefer using their owned-capital. The entrepreneurs expected for focusing on the service quality, raising the selling price while maintaining the quality, and innovating their business to have a different character than competitors. Good relationships with consumers must be maintained so that loyalty customer can achieve.